CINNAMON CLUB RULES. Issue 2 (14th May 2013) - Crainer, Stuart
Abstract : The Cinnamon Club chef and CEO, Vivek Singh has led a culinary revolution, developing signature dishes and a powerful brand. He reveals his approach to leadership, innovation and growth toStuart Crainer .